2005
DOI: 10.1093/glycob/cwi097
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Siglec-F and human Siglec-8 are functionally convergent paralogs that are selectively expressed on eosinophils and recognize 6′-sulfo-sialyl Lewis X as a preferred glycan ligand

Abstract: Mouse sialic acid-binding immunoglobulin-like lectin F (Siglec-F) is an eosinophil surface receptor, which contains an immunoreceptor tyrosine-based inhibitory motif (ITIM) in its cytoplasmic domain, implicating it as a regulator of cell signaling as documented for other siglecs. Here, we show that the sialoside sequence 6'-sulfo-sLe(X) (Neu5Acalpha2-3[6-SO4] Galbeta1-4[Fucalpha1-3]GlcNAc) is a preferred ligand for Siglec-F. In glycan array analysis of 172 glycans, recombinant Siglec-F-Fc chimeras bound with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
182
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(189 citation statements)
references
References 54 publications
7
182
0
Order By: Relevance
“…In previous studies, these antibodies have been shown to react similarly with b-series gangliosides GD1b, GT1b, GQ1b, and GD3 in a manner consistent with their minimal epitope being NeuAc␣2,8- [30,31]. As shown in Figure 3A, Ha1 antibody recognized sialic acid-containing glycosides exclusively and showed a strong preference for glycans containing NeuAc␣2,8-NeuAc␣2,3-Gal.…”
Section: Characterization Of Human Ha1 Antibody Which Recognizes Dismentioning
confidence: 52%
See 1 more Smart Citation
“…In previous studies, these antibodies have been shown to react similarly with b-series gangliosides GD1b, GT1b, GQ1b, and GD3 in a manner consistent with their minimal epitope being NeuAc␣2,8- [30,31]. As shown in Figure 3A, Ha1 antibody recognized sialic acid-containing glycosides exclusively and showed a strong preference for glycans containing NeuAc␣2,8-NeuAc␣2,3-Gal.…”
Section: Characterization Of Human Ha1 Antibody Which Recognizes Dismentioning
confidence: 52%
“…The sugar-binding specificities of Ha1 antibody were analyzed by the Consortium for Functional Glycomics (CFG; http://www.functionalglycomics.org/static/consortium) using Glycan Array v2.8 as described previously [30,31]. Briefly, streptavidin-coated microtiter plates (Reacti-Bind NeutrAvidin-coated high-binding capacity black 384-well plates, Pierce, Rockford, IL) were coated with various biotinylated glycosides (30 pmol/well) in PBS, pH 7.4, overnight at 4°C.…”
Section: Glycan Arraymentioning
confidence: 99%
“…Eosinophils in culture were detected and enumerated by cell surface expression of Siglec F (12,13). In a previous study, we found no Siglec F ϩ eosinophils in the bone marrow of ⌬dblGATA mice when gating on the side scatter-high mature granulocyte population (8).…”
Section: Generation and Quantitative Analysis Of Eosinophils In Bone mentioning
confidence: 98%
“…Investigations of Siglec biology have focused on the mouse as a model organism due to the difficulties and limitations associated with this type of research in humans. Recent studies identified murine Siglec-F as the functional paralog of human Siglec-8 based on its expression on mouse eosinophils and its ability to adhere to the 6′-sulfo-sLex structure (Tateno et al, 2005;Bochner, 2009). Studies have demonstrated that cross-linking of Siglec-F with a specific antibody (Ab) induced mouse eosinophil apoptosis in vivo and in vitro (Zimmermann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%